Identifying the energy consumption to material removal rate in abrasive cutting process using the thin grinding wheel - Yudiyanto, Eko; Adiwidodo, Satworo; Susilo, Sugeng Hadi; Pranoto, Bayu (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the abrasive cutting process using thin grinding wheels, which is applied for cutting materials with various mechanical properties. The problem to be solved is mapping the energy consumption characteristics in this process through the control of cutting parameters such as grinding wheel thickness and feed rate. An experiment was conducted using grinding wheels with 1.2, 1.6, 2.0, and 3.0 mm for cutting metals. Various feed rates were used to cut Al, ST37, and cast iron, which are ductile, ductile-hard, and brittle materials. The results of the experiment show an inverse exponential relationship between the feed rate and specific energy. The 1.2 mm grinding wheel consumes up to 10% less power than the 3.0 mm wheel at low feed rates. The mapping of these characteristics enables the selection of recommended parameters. Achieving stability during the cutting process of ductile materials, the utilization of a 1.6 mm grinding wheel operating at a feed rate of 0.166 mm/s. The rigidity of the wheel determines the stability of the rotation, which depends on the thickness of the grinding wheel. The thickness of the grinding wheel determines the material removal rate of the abrasive process. Ductile-hard materials, such as ST37, require more energy because the abrasive particles must be able to break down the properties of the material to erode its surface. Ductile materials tend to cause high friction and generate heat, melting the material. The space between the abrasive particles can be filled with liquid material, causing BUE to cover the cutting edge of the abrasive particles. The application of the outcome is aimed at the machining, as a scientific basis for energy control at the manufacturing process